Characterization of Lentil Varieties Based on Morphological and Biochemical Tests at Seed and Seedling Stages - D. KHARE; SHUBHANGI GOSAVI; RAJANI TOMAR; KANCHAN SINGH (Seed Research, 2026)
Expressions of four morphological and reaction to six biochemical tests were performed on 25 varieties of lentil to observe distinguishing, uniform and stable expressions over three generations. Expression of seed coat colour, testa mottling and seedling pigmentation are designated as the most stable, uniform and distinguishable traits. Expression of the seed size is not stable for medium and bold seeded varieties. Among the biochemical tests performed for verification of varieties, use of phenol colour, KOH-bleach, HCI test and response of GA, on root and shoot elongation are advocated.